Analysis of physical activity levels and influencing factors in cancer survivors after pancreaticoduodenectomy - Qiuju Tian; Meiqin Xue; Leying Chen; Min Zhang; Weiyi Zhu; Beiwen Wu (Frontiers in Oncology)
IntroductionPhysical activity is becoming more important in cancer patient care. However, there are limited studies investigating physical activity levels in cancer survivors after pancreaticoduodenectomy. This study aims to assess the present status of physical activity levels in cancer survivors after pancreaticoduodenectomy and whether perioperative metrics and length of follow-up have an impact on physical activity levels in survivorship.MethodsThis is a cross-sectional study. The study included cancer survivors who were treated at a tertiary general teaching hospital for pancreaticoduodenectomy from December 2019 to January 2022 following surgery. We quantified physical activity frequency, duration, and intensity using the International Physical Activity Questionnaire-Short Form. Patient demographic and clinical characteristics were obtained via an electronic medical record system. Postoperative complication data were obtained from our survival cohort. Variables univariately associated with the physical activity level at an alpha level of less than 0.1 were included in the logistic regression analysis of factors influencing physical activity in cancer survivors after pancreaticoduodenectomy.ResultsA total of 223 patients who met the eligibility criteria completed a telephone survey. The main form of physical exercise is walking, 69.5% of participants’ physical activity belongs to the active category, but only 16.6% of participants met the aerobic guideline. Logistic regression showed that cancer survivors without pancreatic fistula were 2.453 times more likely to perform active physical activity in survival than those with pancreatic leakage (p = 0.041). For a one-unit increase in operation duration, there is approximately a 0.5% reduction in the level of active physical activity participation among cancer survivors after pancreaticoduodenectomy (p = 0.015). For each unit increase in follow-up time, post-pancreaticoduodenectomy patients were 1.046 times more likely to participate in active physical activity (p = 0.030).ConclusionAlthough half of the cancer survivors after pancreaticoduodenectomy experienced active physical activity, only a small percentage of individuals met the guideline-recommended level of aerobic exercise. More physical activity support should be provided to cancer survivors after pancreaticoduodenectomy. Moreover, operation duration, postoperative pancreatic fistula, and follow-up time should be taken into consideration when giving exercise instructions to postoperative survivors of pancreaticoduodenectomy.